Mushroom marvels: understanding their role in human health - Noreen, Sana; Sultan, Hazeefa; Hashmi, Bushra; Aja, Patrick Maduabuchi; Atoki, Ayomide Victor (Frontiers in Nutrition, 2025)
Edible mushrooms have long been valued not only for their culinary appeal but also for their significant nutritional and medicinal properties. This review examines the chemical composition, nutritional value, and bioactive potential of various edible mushroom species. Mushrooms are rich in moisture, proteins, fibers, vitamins, minerals, and a diverse array of bioactive compounds, including phenolic acids, flavonoids, sterols, polysaccharides, and terpenoids. These components confer a range of health benefits, notably antioxidant, anti-inflammatory, anti-microbial, anti-diabetic, hepatoprotective, neuroprotective, and immunomodulatory effects. Furthermore, the review emphasizes the industrial applications of mushrooms in pharmaceuticals, nutraceuticals, cosmeceuticals, agriculture, and biotechnology. Despite their benefits, certain mushroom species pose toxicological risks due to compounds like amatoxins and ibotenic acid, underscoring the importance of proper identification and consumption practices. This study aims to bridge traditional knowledge and modern scientific insights, thereby supporting the integration of mushrooms into functional foods and therapeutic regimens that enhance human health and well-being.